Effect of alternative modes of application on microleakage of one-step self-etch adhesives - Mustafa Ulker; Hayriye Esra Ulker; Said Karabekiroglu; Murat Selim Botsali; Ali Riza Cetin (Elsevier, 2013)
Background/purpose: Contemporary one-step self-etch adhesives are certainly the most user-friendly adhesives; however, typically could not compete with the more traditional multi-step adhesives. This in vitro study evaluated the efficacy of two modes of application (double application or placement of a hydrophobic resin coating) for the reduction of microleakage, using three different one-step self-etch adhesives (AdheSE One VivaPen, Ivoclar Vivadent, Schaan, Liechtenstein; Xeno V, Dentsply De Trey, Konstanz, Germany; OptiBond All-In-One, Kerr Italia S.r.l, Scafati, Italy). Materials and methods: We prepared Class V cavities with the occlusal margin in enamel and gingival margin in dentin on both buccal and lingual surfaces of 108 human molar teeth. Cavities were divided into nine groups according to the combination of adhesives and application modes used (n = 24). For applying adhesives, we followed three types of procedures: (1) according to the manufacturers' directions; (2) using a double-application method; and (3) with the additional placement of a hydrophobic resin layer after following the manufacturers' directions. We restored the cavities with a composite resin. After thermocycling (500 cycles at 5°C/55°C) and immersion in 0.5% basic fuchsin, we sectioned the teeth and evaluated them for microleakage using a stereo microscope (20×). Enamel and dentin margins were scored separately, and we analyzed the data using Kruskal-Wallis, Bonferroni-corrected Mann-Whitney U, and Wilcoxon signed-rank tests. Results: Application of a hydrophobic resin over the cured Xeno V adhesive decreased the amount of microleakage at the enamel margins, compared with the application according to the manufacturer's instructions (P = 0.005). Both application modes decreased the amount of microleakage at the dentin margins with AdheSE One VivaPen adhesive, compared with application according to the manufacturer's instructions (P < 0.001). With the OptiBond All-In-One adhesive, no significant difference between application modes was observed. Conclusion: Alternative modes of application did not adversely affect the sealing ability of one-step self-etch adhesives. Depending on the type of adhesive, alternative modes of application may contribute to low microleakage values.